The Data Horror Escape Room game as a successful tool for RDM education and engagement - Karvovskaya, Lena; Yeomans, Joanne; Rodenburg, Elisa (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2025)
This paper presents a case study of how researchers can be engaged with the topic of Research Data Management in a playful and interesting way. The case in point is the Data Horror Escape Room, developed in 2020, a successful tool for facilitating discussion about research data management during educational, social, and peer-to-peer events. Escape rooms are games that are completed by solving a collection of puzzles and have been shown to be useful tools for game-based learning. The paper reflects on the steps that led to creation of the game, including its technical implementation using Google Sites and gives an overview of how the game was used and feedback it received. Readers are welcome to use the paper as guidance for reusing the escape room for their own events or as inspiration for building a similar escape room for their own purpose. The Data Horror Escape Room is openly available to access through a URL, and is archived as a dataset in Zenodo.